Efficient conversion of glucose into 5-hydroxymethylfurfural using a bifunctional Fe3+ modified Amberlyst-15 catalyst. Issue 2 (5th December 2018) - Xu, Siquan; Yin, Chunyu; Pan, Donghui; Hu, Feng; Wu, Yuanfeng; Miao, Yanan; Gao, Lijing; Xiao, Guomin
Abstract : In this study, a series of Fe 3+ modified Amberlyst-15 resins (Fe/AR) were prepared and used as environmentally friendly bifunctional catalysts for the conversion of glucose to 5-hydroxymethylfurfural (HMF). Abstract : In this study, a series of Fe 3+ modified Amberlyst-15 resins (Fe/AR) were prepared and used as environmentally friendly bifunctional catalysts for the conversion of glucose to 5-hydroxymethylfurfural (HMF). The physicochemical properties of the Fe/AR catalysts were characterized by XRD, SEM-EDX, XPS, TG-DTA and FTIR spectroscopy techniques. It was found that the 10%-Fe/AR catalyst has the ability to synergistically catalyze the isomerization of glucose and the dehydration of fructose in a "one-pot" reaction, and allows an impressive 68% HMF yield to be achieved in the H2 O/THF biphasic system. Moreover, the 10%-Fe/AR catalyst still retained the desired catalytic activity after four consecutive cycles.